Impact of Different Treatment Modalities on Vitamin D3 and Oxidative Stress Markers in Serum and Saliva of Iraqi Patients with Behçet’s Disease - Qabas A. Mohammed; Ban AL-Drobie; Hayder A. Hasan (مجلة كلية الطب)
Background: It is believed that vitamin D is a major environmental factor that can affect the occurrence of many inflammatory and autoimmune disorders, such as Behcet's disease. Objectives: To evaluate the impacts of medical treatment and body mass index on vitamin D3 and certain oxidative stress markers (Glutathione, Nitric Oxide) in Iraqi patients afflicted by Behcet disease. Additionally, it sought to explore any potential correlations between such markers and Vitamin D3 with the severity of Behcet disease, and the diagnostic potential of saliva in measuring such markers. Methods: This is a case-control study conducted at Merjan Teaching Hospital in Babylon City between December 2023 and March 2024. Forty-five patients suffering from Behcet disease, and meeting international criteria, were divided into three groups: 15 on azathioprine treatment, 15 newly diagnosed untreated cases, and 15 on anti-TNF-α (Infliximab) biological therapy. A control group of 15 subjects matched for age and sex were included. Serum and salivary 25-hydroxy vitamin D levels were measured using enzyme-linked immunosorbent assay. Spectrophotometric methods were used to assess levels of reduced Glutathione and Nitric Oxide in serum and saliva across the groups. Statistical Package for the Social Sciences software, version 26 was used to analyze data. A significance level of P ≤ 0.05 has been established as statistically significant. Results: Vitamin D3 level was significantly lower in newly diagnosed Behcet disease patients as well as those on Infliximab therapy compared with controls. The greatest serum Glutathione level was found in cases of Infliximab treatment compared with other groups. Serum Nitric Oxide showed an inverse correlation with a highly significant difference in disease severity. Conclusion: Newly diagnosed Behcet disease cases and those on Infliximab therapy were linked to vitamin D deficiency. A positive correlation between serum and salivary D3 was established. Salivary Nitric Oxide increased during Behcet disease. Since serum Nitric Oxide levels fall as the disease progresses, it could evaluate the severity of Behcet disease.